Análise do processo de adaptação ao mercado de trabalho dos formandos de um curso superior de ciências contábeis no Brasil: o caso dos egressos da Universidade Federal de Mato Grosso - Leite, Isler Silveira (1989)
The purpose of this paper was to verify the adjustment to labor market conditions of people who concluded Accounting Science Course in Mato Grosso Federal University, specifically those who finished it in 1983 (CHAPTER I). A reading of the literature presents a retrospective view of Accounting teaching evolution in Brazil and develops the Research Referential project (CHAPTER 11). Next, the author describes the methodology he used and the reasons for his choice (CHAPTER 111). The research data had been collected through open and closed questions, aiming to facilitate their organization. 50 it was possible to describe the characteristics of each case (CHAPTER IV). From these results, it was possible to analyze the particularities of Accounting teaching at Mato Grosso Federal University, the profile of the Accounting Science Course concluders and their adaptation to the labour market (CHAPTER V). Finally, the author presents a research summary, containing some conclusions and suggestions to further study (CHAPTER VI).